Ancestral Stem Cell Reprogramming Genes Active in Hemichordate Regeneration - Humphreys, Tom; Weiser, Keith; Arimoto, Asuka; Sasaki, Akane; Uenishi, Gene; Fujimoto, Brent; Kawashima, Takeshi; Taparra, Kekoa; Molnar, Janos; Satoh, Noriyuki; Marikawa, Yusuke; Tagawa, Kuni (Frontiers in Ecology and Evolution, 2022)
Hemichordate enteropneust worms regenerate extensively in a manner that resembles the regeneration for which planaria and hydra are well known. Although hemichordates are often classified as an extant phylogenetic group that may hold ancestral deuterostome body plans at the base of the deuterostome evolutionary line leading to chordates, mammals, and humans, extensive regeneration is not known in any of these more advanced groups. Here we investigated whether hemichordates deploy functional homologs of canonical Yamanaka stem cell reprogramming factors, Oct4, Sox2, Nanog, and Klf4, as they regenerate. These reprogramming factors are not expressed during regeneration of limbs, fins, eyes or other structures that represent the best examples of regeneration in chordates. We first examined Ptychodera flava EST libraries and identified Pf-Pou3, Pf-SoxB1, Pf-Msxlx, and Pf-Klf1/2/4 as most closely related to the Yamanaka factors, respectively. In situ hybridization analyses revealed that all these homologs are expressed in a distinct manner during head regeneration. Furthermore, Pf-Pou3 partially rescued the loss of endogenous Oct4 in mouse embryonic stem cells in maintaining the pluripotency gene expression program. Based on these results, we propose that hemichordates may have co-opted these reprogramming factors for their extensive regeneration or that chordates may have lost the ability to mobilize these factors in response to damage. The robustness of these pluripotency gene circuits in the inner cell mass and in formation of induced pluripotent stem cells from mammalian somatic cells shows that these programs are intact in humans and other mammals and that these circuits may respond to as yet unknown gene regulatory signals, mobilizing full regeneration in hemichordates.